Drosophila Mi-2 Negatively Regulates dDREF by Inhibiting Its DNA-Binding Activity - Hirose, Fumiko (American Society for Microbiology, 2002)
Drosophila melanogaster DNA replication-related element (DRE) factor (dDREF) is a transcriptional regulatory factor required for the expression of genes carrying the 5′-TATCGATA DRE. dDREF has been reported to bind to a sequence in the chromatin boundary element, and thus, dDREF may play a part in regulating insulator activity. To generate further insights into dDREF function, we carried out a Saccharomyces cerevisiae two-hybrid screening with DREF polypeptide as bait and identified Mi-2 as a DREF-interacting protein. Biochemical analyses revealed that the C-terminal region of Drosophila Mi-2 (dMi-2) specifically binds to the DNA-binding domain of dDREF. Electrophoretic mobility shift assays showed that dMi-2 thereby inhibits the DNA-binding activity of dDREF. Ectopic expression of dDREF and dMi-2 in eye imaginal discs resulted in severe and mild rough-eye phenotypes, respectively, whereas flies simultaneously expressing both proteins exhibited almost-normal eye phenotypes. Half-dose reduction of the dMi-2 gene enhanced the DREF-induced rough-eye phenotype. Immunostaining of polytene chromosomes of salivary glands showed that dDREF and dMi-2 bind in mutually exclusive ways. These lines of evidence define a novel function of dMi-2 in the negative regulation of dDREF by its DNA-binding activity. Finally, we postulated that dDREF and dMi-2 may demonstrate reciprocal regulation of their functions.